DL-3-n-butylphthalide for acute ischemic stroke: An updated systematic review and meta-analysis of randomized controlled trials - Wang, Huan; Ye, Kaili; Li, Dan; Liu, Yuxin; Wang, Deren (Frontiers in Pharmacology, 2022)
Background DL-3-n-butylphthalide (NBP) is widely used as a neuroprotective drug in stroke patients in China. A systematic review in 2010 suggested NBP to be safe and effective at promoting neurological recovery, but could not conclude whether it decreased risk of long-term death or disability. Since numerous randomized controlled trials (RCTs) have been conducted on NBP since 2010, we performed an updated systematic review and meta-analysis of safety and efficacy data. Method We searched electronic databases and reference lists to identify RCTs that compared patients who received NBP or not (including placebo). Methodological quality of RCTs was assessed using the Revised Cochrane Risk of Bias Tool 2.0, and data were meta-analyzed using Review Manager 5.4 software. Results Fifty-seven RCTs involving 8,747 participants were included. Twenty trials examined NBP as a capsule, 29 as an injection, and 8 as sequential injection-capsule therapy. Meta-analyses showed that NBP treatment was associated with a reduction in composite outcome of death and dependency (risk ratio 0.59, 95% CI 0.42 to 0.83; 260 participants; 2 studies), death (risk ratio 0.32, 95% CI 0.13 to 0.75; 2,287 participants; 10 studies), modified Rankin Scale score (mean difference -0.80, 95% CI -0.88 to -0.72; 568 participants; 4 studies), and an increase in Barthel Index, which assesses the ability to engage in basic activities of daily living (mean difference 11.08, 95% CI 9.10 to 13.05; 2,968 participants; 22 studies). Meta-analyses found that NBP significantly reduced neurological deficit based on National Institute of Health Stroke Scale (mean difference -3.39, 95% CI -3.76 to -3.03; 7.283 participants; 46 studies) and Chinese Stroke Scale (mean difference -4.16, 95% CI -7.60 to -0.73; 543 participants; 4 studies). Of the adverse events reported in 31 trials, elevated transaminase (incidence, 1.39-17.53%), rash (0-1.96%) and gastrointestinal discomfort (1.09-6.15%) were most frequent and no serious adverse events were reported. Conclusion This update review confirms that NBP can help acute ischemic stroke patients regain the ability to perform activities of daily living, reduce their neurological deficit and short-term death rates. However, the available evidence on whether NBP reduces risk of long-term death or dependence after ischemic stroke remains insufficient.